How puzzling - Snape, Charles; Scott, Heather (New York : Cambridge University press, 1996)
A lively book featuring a collection of puzzles, problems and activities linked to the history of mathematics. Drawing on the riddles and paradoxes of the great mathematician philosophers of ancient times, as well as the mysteries of the Rubik Cube, it encourage children to think afresh